Signa Vitae 2020
DOI: 10.22514/sv.2020.16.0066
|View full text |Cite
|
Sign up to set email alerts
|

CD82 Aggravates Sevoflurane - Induced Neurotoxicity by Regulating TRPM7 in Developing Neurons

Abstract: Background: Sevoflurane, a commonly used anesthetic in neonatal, could induce neurotoxicity in newborn animals. CD82 was found to be involved in age-related cognitive impairment. However, the role of CD82 in sevoflurane-induced neurotoxicity remains elusive. Methods: Hippocampal neurons were isolated from neonatal rats (postnatal day 1 or 2), and then exposed to 1.8 % sevoflurane for 6, 12, 24 or 48 hours. Neurons were pre-transfected with siRNA targeting CD82 (siCD82) or co-transfected with siTRPM7 (transient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…1 Sevoflurane is an accepted clinical anesthetic with safety and effectiveness that has been frequently used in many types of operations for decades. 4,5 Although the cardioprotective effects of sevoflurane have been well-recognized, the anesthesia-induced cognitive deficits after surgery need more study to be explored. 6 Previous study indicated that sevoflurane administrated adult rats showed impaired spatial memory ability.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Sevoflurane is an accepted clinical anesthetic with safety and effectiveness that has been frequently used in many types of operations for decades. 4,5 Although the cardioprotective effects of sevoflurane have been well-recognized, the anesthesia-induced cognitive deficits after surgery need more study to be explored. 6 Previous study indicated that sevoflurane administrated adult rats showed impaired spatial memory ability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Because the etiology of POCD is related to multiple factors, including the patients, the operation, the anesthesia, or the combinations of them, its internal mechanism is complicated and largely unclear . Sevoflurane is an accepted clinical anesthetic with safety and effectiveness that has been frequently used in many types of operations for decades. , Although the cardioprotective effects of sevoflurane have been well-recognized, the anesthesia-induced cognitive deficits after surgery need more study to be explored . Previous study indicated that sevoflurane administrated adult rats showed impaired spatial memory ability. , In addition, several reports have investigated potential mechanism pathways involved in the cognitive impairments caused by sevoflurane anesthesia, including endoplasmic reticulum stress, mitochondrial stimulation, inflammation, and neuronal apoptosis. It seems that sevoflurane more or less aggravates the cognitive deficits; however, the exact underlying mechanism behind sevoflurane-induced occurrence of POCD is still open.…”
Section: Introductionmentioning
confidence: 99%
“…Preterm babies with immature organ systems and severe congenital defects require surgery and general anesthesia . Anesthetics, including sevoflurane, isoflurane, and propofol, have been shown to induce harmful effects on the developing brain. , For example, isoflurane induced neurocognitive deficits and neurogenetic damage in neonatal rats . Sevoflurane exposure also promoted neuroapoptosis in neonatal rats and induced impairment in learning and memory function .…”
Section: Introductionmentioning
confidence: 99%
“…Neuroinflammation has been reported to contribute to the progress of POCD [4,5]. Clinical studies and experimental evidence have confirmed that anti-inflammatory therapy can reduce POCD [6][7][8].…”
Section: Introductionmentioning
confidence: 96%